The Reform of the Procedural Religious Court Law Based on Islamic Law in Indonesian Legal System - Abdullah Gofar (Faculty of Law, Sriwijaya University, Indonesia, 2017)
The history of the development of religious courts and the inner atmosphere struggle of Muslims in Indonesia which faced the state’s political force in the New Order era has brought forth the religious procedural law. Article 54 of The 1989 Law No.7 stated that